Etude des discontinuités géologiques liées aux calcaires de la carrière de la cimenterie « Col De Beccouche » Sour El Ghozlane, wilaya de BOUIRA - GARTI ,Hanane; DASSAMIOUR, Mohamed (Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2015)
The purpose of this work is the study of fracturing related to the limestone quarry in Col De Beccouche to determine favorable directions to dislocation of the blocks during the operation work. The study of these fractures is made by the analysis of measurements made on the ground by statistical methods and projection. Three families of discontinuities were identified: (1) The average family F1 steering N89,6 °; (2) The family F2, a direction with an average of N123,2 °; 3) The family F3, average direction N141 °. Consideration of the Col de Beccouche structure that takes the form of anticline has identified the potential directions to dislocation of the blocks.